In A Low-Resource Environment, Informatics Solutions Can Help Close the Gap between Clinical Nursing and Laboratory Services - Fahad Hussein Alradhi; Zaher Ahmed Hassan Alali; Mohammed Jawad Alabed; Moyad Abdullah Alali; Zainab Salman Abdullah Almulla; Aqeel Ibrahim Busbaih; Kawther Ali Al Salim; Ayman Matooq Alsalman; Dalal Matooq Alsalman; Ahmed Yousef Ali Al Yousef (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Healthcare systems in low-resource settings face significant challenges in maintaining efficient laboratory services, which are crucial for diagnosing and managing diseases like HIV, tuberculosis, and malaria. The absence or underutilization of laboratory diagnostics can lead to misdiagnoses, inappropriate treatments, and increased drug resistance. However, gaps in laboratory operations, particularly in data management and workflow, are underexplored, and the potential role of informatics in addressing these issues remains largely untapped. Methods: This study was conducted at a tertiary healthcare facility serving over four million people, utilizing previously collected data and quality improvement assessments. The research focused on the laboratory's operations, including the demand for services, prevalence of untestable samples, workflow, and time required for result reporting. Data were gathered from laboratory records over a one-year period and supplemented by a four-week audit of 3,549 samples. Workflow analysis was used to identify informational barriers at critical stages in the testing process, including pre-analytical, analytical, and post-analytical phases. Results: The audit revealed that 54% of samples were untestable, with insufficient sample volume as the primary cause, particularly in the pediatric department. The laboratory conducted 242,242 tests during the study period, with parasitology and blood bank departments handling the largest volumes. Workflow analysis identified several challenges, including incomplete test requisition forms, improper sample labeling, and delays in sample transport and result reporting. On average, results took just under six hours to be collected, with some results remaining uncollected for over 16 hours. Conclusion: The study highlights significant informational barriers in laboratory operations, particularly in the pre- and post-analytical stages. These challenges, including poor communication and inefficient data handling, undermine laboratory efficiency and effectiveness. Informatics-based solutions could improve data management, streamline communication, and enhance laboratory service delivery in resource-constrained settings, ultimately improving healthcare outcomes. Further research is needed to design, implement, and evaluate such informatics interventions.